2006
DOI: 10.1128/iai.74.1.425-434.2006
|View full text |Cite
|
Sign up to set email alerts
|

GroEL ofLactobacillus johnsoniiLa1 (NCC 533) Is Cell Surface Associated: Potential Role in Interactions with the Host and the Gastric PathogenHelicobacter pylori

Abstract: Heat shock proteins of the GroEL or Hsp60 class are highly conserved proteins essential to all living organisms. Even though GroEL proteins are classically considered intracellular proteins, they have been found at the surface of several mucosal pathogens and have been implicated in cell attachment and immune modulation. The purpose of the present study was to investigate the GroEL protein of a gram-positive probiotic bacterium, Lactobacillus johnsonii La1 (NCC 533). Its presence at the bacterial surface was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
191
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(202 citation statements)
references
References 57 publications
7
191
1
3
Order By: Relevance
“…13 As far as commensal and/or probiotic bacteria are concerned, studying extracellular-surface proteomes allows us to discover proteins involved in bacterial-host cross-talk such as chaperones and moonlighting glycolytic enzymes, 14,15 immune system modulators 16 and proteins involved in adhesion to biotic surfaces. [17][18][19] In recent years, one of the applications of probiotics is represented by their use as nutraceutical supplements; they can be supplemented with zinc, selenium, vitamins and o-3-fatty acids, in order to enhance beneficial effects on human health. 20,21 Selenium (Se) is a fundamental trace element for humans, since its deficiency has been correlated to several diseases (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…13 As far as commensal and/or probiotic bacteria are concerned, studying extracellular-surface proteomes allows us to discover proteins involved in bacterial-host cross-talk such as chaperones and moonlighting glycolytic enzymes, 14,15 immune system modulators 16 and proteins involved in adhesion to biotic surfaces. [17][18][19] In recent years, one of the applications of probiotics is represented by their use as nutraceutical supplements; they can be supplemented with zinc, selenium, vitamins and o-3-fatty acids, in order to enhance beneficial effects on human health. 20,21 Selenium (Se) is a fundamental trace element for humans, since its deficiency has been correlated to several diseases (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of H pylori-induced proinflammatory factor production by Lactobacilli is a very important aspect. It has been demonstrated that Lactobacilli abrogate H pylorimediated IL-8 release in vitro and in vivo [31,32] . A large body of evidence has shown that H pylori-LPS-induced inflammation in gastric mucosa has nearly the same pathological characteristics as the mucosal inflammation initiated by H pylori infection [6,7] .…”
Section: Viable Lbg or Lbg-s Inhibited H Pyloriss1-lps-induced Il-8 Pmentioning
confidence: 99%
“…Adhering protein molecules characterized from Lactobacillus are Mucus-binding protein (Mub) of L. reuteri 1063 (Roos & Jonsson, 2002), the lectine-like mannose-specific adhesin (Msa) of L. plantarum WCFS1 (Pretzer et al, 2005), the mucus adhesion promoting protein (MAPP or MapA) from L. reuteri 104R reported by its ability to bind porcine mucus and mucin (Rojas et al, 2002) and Caco-2 cells (Miyoshi et al, 2006) and the Mub of L. acidophilus NCFM (Buck et al, 2005). Moreover, two proteins EF-Tu (Elongation Factor-Tu) and GroEL (a class of heat shock protein) of L. johnsonii La1 NCC533 showed abilities to adhere to mucins at specific conditions of pH (Granato et al, 2004;Bergonzelli et al, 2006). Recently a piglet mucus adhesion protein was completely characterized from the potential probiotic L. fermentum strain BCS87 (Macías-Rodríguez et al, 2009).…”
Section: Adhering Probiotic Lactobacillusmentioning
confidence: 99%